Household Waste Management Challenges: The Case of M’sila, Algeria - Naghel, M.; Farhi, A.; Redjem, A. (Engineering, Technology & Applied Science Research, 2022)
Household waste and uncontrolled urbanization management are considered major problems in African countries. In the Hodna region, the phenomenon seems to be more important in urban centers because of the huge amount of household waste generated by domestic and commercial activities. In most Algerian cities, solid waste is piled up in huge quantities in dumps and is dumped indiscriminately in waterways and public spaces. Uncontrolled urbanization, industrial development, and the evolution of lifestyle lead to increased production of waste, whereas the waste management techniques used in urban areas should be reconsidered. From this perspective, this paper studies and analyses in a spatio-temporal approach, the practices of household waste management in the city of M’sila in order to evaluate the state of such management and identify the key elements of integrated planning of waste management.